Pemanfaatan Beberapa Jenis Arang Aktif sebagai Bahan Absorben Logam Berat Cadmium (Cd) pada Tanah Sedimen Drainase Kota Medan sebagai Media Tanam - Rahman, Abdul; Aziz, Rizal; Indrawati, Asmah; Usman, Muhammad (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2020)
The purpose of this two-year research is to find methods and theories of soil cultivation for the Medan city drainage sediment which makes the city drainage shallow. Improving the environmental quality of Medan city by cultivating trench sediment soil into a horticultural planting medium. Obtaining a neat, comfortable and helpful city condition for the Government, especially the Public Works Office of Medam City. It will be avoided from flooding due to smooth city drainage and clean environment. The results of the study can be concluded that the activated charcoal treatment is used from a number of activated charcoal ingredients (Coconut Shell, Wood Sawdust Waste and Kendaga Karet) with measurement criteria namely char yield, water content, ash content, volatile content, carbon fish power, iodine absorption from as a whole it has a good value to be used as activated charcoal which has a value above the minimum limit, namely water content below the maximum value (<15%), ash content <10%, carbon binding capacity> 60%, evaporation power <25% and iodine absorption. > 750 mg. All of these parameters are in accordance with the national standard of SNI 06-3730-1995. The second conclusion is that the absorption of metals to heavy metalsPb, Cd and Cu, has a good ability even though it is small because the metal content from the start is below the quality standard, the concentrations tested are 0, 1, 3, 5, 7, and 9. While the best is obtained of the reduction rate in heavy metal Cd, and is 7 grams / kg of soil sample.Keywords:Â